Transforming Sugarcane Bagasse and Vinasse Wastes into Hydrochar in the Presence of Phosphoric Acid: An Evaluation of Nutrient Contents and Structural Properties - Melo, Camila Almeida [UNESP] (2017)
Purpose: Sugarcane bagasse and vinasse are wastes generated at large scales by the Brazilian sugarcane industry. Therefore, new waste treatment and management practices are essential for a sustainable industrial growth and here we purpose the hydrothermal carbonization (HTC) to converts wet biomass into carbon-based solids. Methods: HTC of a mixture of sugarcane bagasse and vinasse was conducted at different temperatures, reaction times and phosphoric acid percentages. The chemical, structural and morphological properties of the hydrochars were evaluated by elemental analysis (CHNS), nutrient quantification (P, Ca, Mg, K), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and scanning electron microscopy (SEM). Results: In the presence of phosphoric acid, the hydrochar yield increased as the ash content increased due to phosphate precipitates, as observed by XRD. The yield of the hydrochar decreased and the carbon and nitrogen content increased when the temperature increased from 180 to 230 °C. Hydrochars are amorphous and compositionally similar to lignites. The FTIR spectra showed bands at approximately 1700 and 1600 cm−1 in the hydrochar due to carboxylation and aromatization of the products, respectively. The presence of carboxylic acids is important due to their ability to interact with cations and hydrophilic molecules. Additionally, nutrients such as P, N, K, Ca, and Mg were concentrated in the hydrochar as inorganic phases. Conclusions: HTC applied to sugarcane bagasse and vinasse wastes produces hydrochars primarily containing carbon, nitrogen, and other nutrients as inorganic phases. Hydrochars could potentially be used as an agricultural fertilizer. Graphical Abstract: [Figure not available: see fulltext.].